2010
DOI: 10.1016/j.ijpe.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global manufacturing virtual networks in the aeronautical industry

Abstract: Keywords: Global manufacturing virtual network Manufacturing strategies Mass customization Aeronautical industryThe evolution of organizations that work in multinational environments has considerably altered their production strategies. One of the consequences has been the appearance of Global Manufacturing Virtual Networks (GMVNs), which include all kinds of enterprises and production centres and establish a new type of horizontal collaboration and relations between independent companies and even competitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, Hewlett-Packard, IBM, Dell, Procter and Gamble have forged long-term, collaborative relationships with their suppliers to reduce transaction costs and achieve a stronger competitive position (Ramanathan and Gunasekaran, 2014). Rodríguez and Vilana (2010) analyse the practice of Rolls Royce based on three vectors: the globalization of internal processes; the supply and value chains of all the centres involved; and strategic alliances with A C C E P T E D M A N U S C R I P T companies outside the organization. They conclude the collaboration network is based on greater ‗virtualization', and it is becoming more common and efficient at meeting the market requirements, to reduce risk and access new market and seamlessly incorporate.…”
Section: Supply Chain Collaborationmentioning
confidence: 99%
“…For example, Hewlett-Packard, IBM, Dell, Procter and Gamble have forged long-term, collaborative relationships with their suppliers to reduce transaction costs and achieve a stronger competitive position (Ramanathan and Gunasekaran, 2014). Rodríguez and Vilana (2010) analyse the practice of Rolls Royce based on three vectors: the globalization of internal processes; the supply and value chains of all the centres involved; and strategic alliances with A C C E P T E D M A N U S C R I P T companies outside the organization. They conclude the collaboration network is based on greater ‗virtualization', and it is becoming more common and efficient at meeting the market requirements, to reduce risk and access new market and seamlessly incorporate.…”
Section: Supply Chain Collaborationmentioning
confidence: 99%
“…Positioning supply chains as key elements of collaborative networks was already present in the early work of Li et al (2000), in which the term "Global Manufacturing Virtual Network" was suggested. This term is also used in (Rodriguez Monroy et al, 2010) in which the case of the aeronautical industry is considered: in this article are analyzed the causes and conditions of formation of such networks in the sector, trust being again considered as a mechanism for avoiding opportunistic behaviors, and as a mean to overcome the fear inherent to collaborating with external companies. Nevertheless, the article is mainly oriented on the strategic level, and does not address practical issues linked to exchanges of materials.…”
Section: Collaborative Networkmentioning
confidence: 99%
“…In global manufacturing paradigm, there is a growing collaboration through different manufacturing networks and production units. 47,48 This collaboration is necessary due to its results like enabling the manufacturing enterprises for efficient response to market demands and obtaining competitive advantages. 49,50 The collaborative manufacturing agents need to exchange their ideas with their colleagues who are distributed in geographical locations.…”
Section: Additive Manufacturing Necessities Based On a Global Perspecmentioning
confidence: 99%